Mapping Conversation Analysis Studies in the Arab World: Applications and Implications - H. Al-Nofaie (Дискурс профессиональной коммуникации, 2023)
This scoping review investigates the applications and implications of the conversation analysis approach in the Arab world. Specifically, it examines the implementation of conversation analysis by Arab linguists in both foreign language classrooms and social interaction settings. The review identifies gaps in the relevant literature to guide future research. This scoping review is underpinned by the five-stage framework developed by Arksey and O’Malley. The findings reveal that, compared to non-Arab contexts, the literature on this topic in the Arab world is scarce, but there is a growing interest among Arab linguists. The majority of studies reviewed were conducted in college-level English classes, and there is a dearth of studies in school contexts. The studies were categorized based on themes, including the implementation of conversation analysis, context, educational level, type of methodology, and the journal. The findings from interaction in foreign language classrooms were promising, as they provided insights into how learning opportunities might be developed to facilitate teachers’ professional training. Findings related to social interaction, although limited in number, revealed important features of human interaction, such as topic shifting, ending conversations, and the functions of religious markers. The paper concludes with a discussion of the challenges in implementing conversation analysis and calls for future research on this promising approach in the Arab world.